2009
DOI: 10.3310/hta13440
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness and cost-effectiveness of cochlear implants for severe to profound deafness in children and adults: a systematic review and economic model

Abstract: How to obtain copies of this and other HTA programme reports An electronic version of this publication, in Adobe Acrobat format, is available for downloading free of charge for personal use from the HTA website (www.hta.ac.uk). A fully searchable CD-ROM is also available (see below).Printed copies of HTA monographs cost £20 each (post and packing free in the UK) to both public and private sector purchasers from our Despatch Agents.Non-UK purchasers will have to pay a small fee for post and packing. For Europea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
230
1
11

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(254 citation statements)
references
References 18 publications
12
230
1
11
Order By: Relevance
“…A cochlear implant is an electronic device which restores partial hearing to people who are profoundly deaf. By stimulating the auditory nerve directly via an electrode array which has been surgically implanted into the inner ear (the cochlea), cochlear implantation restores the audibility of sounds (Bond et al, 2009). However, the signals that implantees receive are degraded spectrally (they receive fewer channel of information) and temporally (limited to slow fluctuations in amplitude over time).…”
mentioning
confidence: 99%
“…A cochlear implant is an electronic device which restores partial hearing to people who are profoundly deaf. By stimulating the auditory nerve directly via an electrode array which has been surgically implanted into the inner ear (the cochlea), cochlear implantation restores the audibility of sounds (Bond et al, 2009). However, the signals that implantees receive are degraded spectrally (they receive fewer channel of information) and temporally (limited to slow fluctuations in amplitude over time).…”
mentioning
confidence: 99%
“…Si bien existen diversos estudios que reconocen la efectividad y la costo efectividad del implante coclear precoz en niños con hipoacusia sensorioneural severa y profunda [7][8][9][10] , un alto porcentaje de esta población infantil no accede a esta intervención, tanto por cobertura insuficiente en los servicios sanitarios [11][12][13] como por factores económicos y étnicos de exclusión social [13][14][15][16] .…”
Section: Introductionunclassified
“…Of the remaining 37 abstracts, 32 were unrelated to comparison of bilateral and unilateral CI in children, or did not consider clinical effectiveness. Two HTA publications (4,5) and three systematic reviews that included comparison of bilateral and unilateral CI in children (6 -8) were used for the HTA report. No relevant high quality primary studies were found that had been published subsequent to material included in the reviews..…”
Section: Efficacy Of Bilateral CImentioning
confidence: 99%